The twentieth-century novel : an introduction - Kershner, R. B., 1944- (Boston : Bedford : Basingstoke : Macmillan, 1997)
Designed to supplement undergraduate and introductory graduate level study of the modern novel, [this book] offers a brief yet complete survey of the history, theory, and issues of the form. Through carefully chosen examples and concise explanation, [the author] introduces students to the basic terminology, explores traditional conceptions of the novel, and traces the form's development through modernism and Postmodernism to the present day. In addition, this volume provides students with a succinct introduction to literary theory and the challenges posed by contemporary approaches to literature, including coverage of feminist, gay and lesbian, African American, and postcolonial criticism. -Back cover.
Theories of the novel -- The rise of modernism -- From modernism to postmodernism -- The novel, race, and nation -- Gender criticism -- Glossary, elements of the novel.
Includes bibliographical references and index.
Keywords: Fiction -- 20th century -- History and criticism; Romans; Literatuurkritiek; Literatuurtheorie